Volume 1C, Symposia: Fundamental Issues and Perspectives in Fluid Mechanics; Industrial and Environmental Applications of Fluid 2014
DOI: 10.1115/fedsm2014-21255
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Flow Around a Generic Car Using Dynamic Mode Decomposition

Abstract: The drag of a car is highly dependent on the topology of its complex wake system. Small changes in the shape of the car, that do not have a big effect when considered separately, can lead to significant changes in the total drag when the vortex systems of the changed part of the car body interact with the wake vortices. To understand these interferences, a method is necessary that decomposes the flow based on dynamic information. In this paper, the feasibility of using the Dynamic Mode Decomposition (DMD) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Before performing DMD analysis, a low-pass filter with 10Hz of cut off frequency is applied on the wall force for the temporal direction by forward-backward filtering with 2nd order Butterworth filter, which results in 4th order zero-phase filter, in addition to filtering performed by SVD. These preprocessing techniques are conducted according to Peichl, et al (4) (Please also refer to Schmid (1) , and Duke, et al (20) regarding sensitivity of dataset on DMD.) Total time length of the dataset used for DMD is 3.5 sec in total and snapshots of the flow field are sampled with ∆ = 0.005sec.…”
Section: Dmd On the Wall Forcementioning
confidence: 99%
See 2 more Smart Citations
“…Before performing DMD analysis, a low-pass filter with 10Hz of cut off frequency is applied on the wall force for the temporal direction by forward-backward filtering with 2nd order Butterworth filter, which results in 4th order zero-phase filter, in addition to filtering performed by SVD. These preprocessing techniques are conducted according to Peichl, et al (4) (Please also refer to Schmid (1) , and Duke, et al (20) regarding sensitivity of dataset on DMD.) Total time length of the dataset used for DMD is 3.5 sec in total and snapshots of the flow field are sampled with ∆ = 0.005sec.…”
Section: Dmd On the Wall Forcementioning
confidence: 99%
“…In the field of applied aerodynamics, Muld, et al (3) analyzed the unsteady flow field around a high-speed train by using DMD, and identified the flow structure related to slip-stream. Peichl, et al (4) applied DMD on the flow field around a road vehicle and discussed the coherent flow structures which are dominant in the unsteady flow field around the vehicle through the results of DMD. In these researches, DMD was applied on the velocity field, but DMD can be applied on any multi-dimensional data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example of DMD analysis in the field of applied aerodynamics, Muld, et al (3) identified the flow structure related to slip-stream behind a highspeed train by applying DMD on the unsteady flow field. Peichl, et al (4) discussed the dominant flow structures in the unsteady flow field around a road vehicle by using DMD.…”
Section: Introductionmentioning
confidence: 99%
“…For vehicle aerodynamics, DMD has been successfully applied to examine CFD data with various objectives. Peichl et al (3) presents the application of conventional DMD on flow field data from a Detached Eddy Simulation of the DrivAer reference body. They suggest preprocessing the flow field data, which filters out numerical noise and high frequency components, in order to generate a Reduced Order Model (ROM).…”
Section: Introductionmentioning
confidence: 99%